Educational frontiers with ChatGPT: a social network analysis of influential tweets - Mehmet Firat; Saniye Kuleli (Alteridad : Revista de Educación)
The unprecedented adoption of OpenAI's ChatGPT, marked by reaching 100 million daily users in early 2023, highlights the growing interest in AI for educational improvement. This research aims to analyze the initial public reception and educational impacts of ChatGPT, using social network analysis of the 100 most influential tweets. Using the ForceAtlas2 algorithm and thematic content analysis, the study explores the appeal of ChatGPT and its prospects as an educational tool. The findings underscore ChatGPT's potential to revolutionize teaching methods, facilitate personalized learning, and bridge gaps in access to quality education. In addition, the analysis sheds light on ChatGPT's role in promoting critical thinking and interactive learning, its utility in creating educational content, and its ability to enhance teacher-student interactions. These findings point to a shift toward AI-enhanced education and argue for the integration of ChatGPT and similar technologies into learning environments. The discussion argues for empirical research on the educational impact of ChatGPT and urges a cautious approach to its adoption. It highlights the need for frameworks that harness the power of ChatGPT while addressing ethical and practical challenges. Finally, this study describes the initial reception of ChatGPT and highlights its transformative potential in education. It calls for strategic AI integration to optimize educational processes, and emphasizes the importance of continued research to navigate the evolving role of AI in learning.